Conflict sociology : A sociological classic updated - Collins, Randall (London Routledge, 2009)
This new edition is a substantial abridgment and update of Randall Collins's 1975 classic, Conflict Sociology. The first edition represented the most powerful and comprehensive statement of conflict theory in its time. Here, Sanderson has retained the core chapters and added discussions on Collins's and others' work in recent years. An afterword summarizes Collins's latest forays into microsociological theorizing and attempts to demonstrate how his newer microsociology and older macrosociology are connected.
Keywords: Sociology; Social conflict